Perancangan Identitas Visual Lembaga Sosial PPAY Baiturrohman - Sari, Nabila Rosyita; El Chidtian, Aileena Solicitor Costa Rica; Yani, Aditya Rahman (Universitas Bumigora, 2023)
Poverty is still one of the unsolved problems in Indonesia. Social institutions or foundations have an important role to play in helping overcome poverty in Indonesia. And one of the Social Institutions that overcomes poverty and helps orphans in the Krian sub-district, Sidoarjo is the Baiturrohman PPAY Social Institution. However, there are many obstacle factors experienced by the Baiturrohman PPAY Social Institution in the process of building brand branding so that the public is not aware of the existence of the Baiturrohman PPAY Social Institution, namely They do not yet have a visual identity that is distinctive and conceptual. This design uses descriptive analysis methods and the TOWS Matrix. This design aims to introduce the Baiturrohman PPAY Social Institution to the wider community through a consistent and characteristic visual identity. The result of this design is a visual identity in the form of a logo with character and can be implemented in various supporting media for the branding of the Baiturrohman PPAY Social Institution.